Development of TPACK-Contained of Light Properties Teaching Materials for Grade IV Elementary School Students - Iswanto, Iswanto; Subali, Bambang; Sutarto, Joko (Journal of Primary Education, 2021)
The teaching materials used by students only based on student books and certain printed worksheets as learning resources and regardless the student’s character in delivering the materials. Teaching materials that have not been able to increase students’ interest in learning of our school. The purpose of this study was to develop teaching materials for the properties of light with Technological Pedagogical Content Knowledge (TPACK) approach in science learning, determine eligibility criteria, and the effect of implementing teaching materials to increase student interest in learning. The research model uses the Sugiyono (2018) development design which is modified into three stages, namely preliminary studies, development, and implementation. Data analysis techniques in the research process include feasibility analysis of teaching materials, N-gain test and Mann Whitney Nonparametric Test to determine the effect of teaching materials on student interest in learning. The results of the study show that (1) the results of validation by experts and practitioners of teaching materials on the properties of light charged with TPACK with an average of 89.53% with very feasible criteria (2) the results of implementing teaching materials can increase students' interest in learning science. This result is evidenced by the average N-gain of the experimental class students of 0.54 (moderate) and the control class students of 0.26 (weak). The results of the Mann Whitney Nonparametric Test obtained the Asymp Sig value < 0.05, then Ho was rejected, this means that there is a significant increase in student interest in learning by using teaching materials for the properties of light with TPACK contain.